2017
DOI: 10.18203/2394-6040.ijcmph20175358
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of external injuries among industrial workers in an urban area of Kancheepuram district, Tamil Nadu

Abstract: Background: Workers engaged in industries and construction sites faced several problems and often work in substandard conditions, getting exposed to various hazards in the work place without appropriate safety training. Injuries among workers are an important health issue in industries. This study was planned to assess the prevalence of external injuries among industrial workers in an industrial area and to identify the association between socio-demographic risk factors and external injuries among the industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
3
2
Order By: Relevance
“…The present study is consistent with a study in Ethiopia that reported about 63.4% occupational injury prevalence among industrial workers [ 46 ]. However, in an urban city in India, Sashidharan and Gopalakrishnan (2017) in a study among industrial workers reported an injury prevalence of 44.3% [ 37 ] which is lower than the prevalence rate (63.4%) observed in our study. In the present study, we estimated injury prevalence among over nine different occupational groups compared to two in the study in India [ 37 ] which could affect the injury rates.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The present study is consistent with a study in Ethiopia that reported about 63.4% occupational injury prevalence among industrial workers [ 46 ]. However, in an urban city in India, Sashidharan and Gopalakrishnan (2017) in a study among industrial workers reported an injury prevalence of 44.3% [ 37 ] which is lower than the prevalence rate (63.4%) observed in our study. In the present study, we estimated injury prevalence among over nine different occupational groups compared to two in the study in India [ 37 ] which could affect the injury rates.…”
Section: Discussioncontrasting
confidence: 84%
“…Data collection was done using a structured questionnaire running on a smartphone with the aid of Kobo Collect. The questionnaire was entirely developed by the investigators through a literature review [ 10 , 17 , 29 , 37 41 ] and has not been validated. Data was collected on socio-demographic variables including age, sex, educational level, monthly salary, type of engagement, health and safety practices such as usage of PPE, frequency of PPE use, access to health and safety training and occurrence of occupational injuries with emphasis on the types, numbers and mechanisms of the injuries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence reported in this study is the same with findings of studies in Gondar city, 38.7% [30]; Maraki campus, University of Gondar, 38.7% [29]; Southeastern Ethiopia, 41.4% [36]; southwestern Ethiopia, 39.2% [37]; Addis Ababa, 38.3% [35]; and Nigeria, 39.25% [38]. The result of this study is lower than the results of other studies in Addis Ababa, 84.7% [31] and 67.7% [39], Iran, 79.8% [40]; Tamil Nadu, 44.3% [41]; and Egypt, 46.2% [42]. The result of this study is also higher than the report of other studies in Gondar, 15% [43]; Uganda, 32.4% [44]; and China 34.82% [45].…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, an individual’s health seeking behavior and its economic impact are potentially driven by his/her vulnerability for poor health, health care expenses, and availability of resources. [ 3 4 5 6 7 ] Construction laborers, often deprived of social security and employee benefits in view of their employment in the unorganized and informal sector, are prone to poor health aggravating their economic condition. [ 3 ] In continuation, there is a gap in understanding the economic impact of catastrophic health expenditure (CHE) (i.e., spending more than 10% of their family income on medical expenses[ 8 ]) incurred among this vulnerable group.…”
Section: Introductionmentioning
confidence: 99%